Pelatihan Penggunaan Geogebra Classroom untuk Mengoptimalkan Pembelajaran Matematika - Aminudin, Mohamad; Basir, Mochamad Abdul; Wijayanti, Dyana; Maharani, Hevy Risqi; Kusmaryono, Imam; Saputro, Bagus Adi (Universitas Nusantara PGRI Kediri, 2021)
GeoGebra Classroom provides solutions for mathematics learners to design online mathematics lessons during the Covid-19 pandemic. The purpose of Community Service (PKM) is to provide mathematics learners with skills to use the GeoGebra Classroom to optimize online mathematics learning. This PKM activity uses an educational approach; that is, this activity has an element of education that can dynamize society towards educational goals. The method used is in the form of online training on the use of GeoGebra Classroom in designing virtual finishes. The training results show that there are positive benefits for this training, teacher motivation to design virtual classes, and teacher activeness in completing independent exercises after the first training session. The main obstacle experienced by participants during online training is the poor signal quality which reduces the quality of sound and video during the training. The results of this training provide skills in designing online mathematics lessons using the GeoGebra Classroom.